Feasibility of Al-Muthalaah Teaching Materials Based on Miles and Huberman Model Analysis and Pancasila Student Profile - Anisa; Asep Sopian; Hanip Hidayatulloh (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Arabic plays an important role in the history of education in Indonesia and must remain as focus of attention. Arabic language learning at MTs under the Ministry of Religious Affairs needs to be well-integrated into the existing curriculum, so that it is relevant to the values promoted by the current vision of Indonesian Education, especially the Pancasila Student Profile which focuses on building the character of students. However, in practice, Arabic language teaching materials at MTs are not fully connected to these values. For this reason, efforts are needed to test the feasibility of one of the teaching materials. In this context, the researcher chose the teaching material